2021
DOI: 10.3233/jnd-210656
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Transthyretin Amyloidosis- Clinical and Genetic Characteristics of a Multiracial South-East Asian Cohort in Singapore

Abstract: Background and aims: Studies of hereditary transthyretin amyloidosis (ATTRv amyloidosis) in South-East Asia are underrepresented in the literature. We report the unique phenotypic and genetic characteristics of this disorder in a multiracial South-East Asian cohort. Methods: Patients with genetically proven ATTRv amyloidosis were identified over a 13-year period (2007–2020) at the National Neuroscience Institute, Singapore. Clinical, laboratory, genotypic and electrophysiological features were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Among those seven patients who died during the follow-up, the cause of death was cardiac in five cases. This mutation was also found in one family recently in Asia [35]. ATTRHis88Arg mutation was reported also as the most common variant in a recent Austrian publication affecting six families [8].…”
Section: Discussionmentioning
confidence: 60%
“…Among those seven patients who died during the follow-up, the cause of death was cardiac in five cases. This mutation was also found in one family recently in Asia [35]. ATTRHis88Arg mutation was reported also as the most common variant in a recent Austrian publication affecting six families [8].…”
Section: Discussionmentioning
confidence: 60%
“…Literature on TTR-related cardiac amyloidosis in Asian populations is limited and is exclusively case series. One such study [ 21 ] demonstrated the genotypic and phenotypic characteristics of familial TTR amyloidosis in a Southeast Asian cohort, where out of 29 patients from China, Malaysia, Myanmar, Vietnam, and Indonesia, 5 patients were found to have early-onset disease (age <50 years) with multiple variants which included Gly47Ala mutation. They have found somatic neuropathy to be the most common initial symptom, followed by carpal tunnel syndrome, as well as autonomic and cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Available literature suggests that the main presenting pathologies of wild-type ATTR are cardiomyopathy, carpal tunnel syndrome, and spinal canal stenosis, while patients with hereditary ATTR present with a higher incidence of gait instability, gastrointestinal symptoms, urinary incontinence, and neuropathic pain 14,20,21 ; clinical experience suggests that these differences in presenting pathologies are also found in different populations of Asian patients. [22][23][24][25] Concomitant ATTR amyloidosis and severe aortic stenosis has been reported to be a relatively common finding in the elderly Indian population. 26 For hereditary ATTR in the Asian population, Ala97Ser (p.A97S) appears to be the most commonly identified mutation 23,24 | 899 (p.His108Arg), and ATTR-A97S (p.Ala117Ser).…”
Section: Suspecting Attr-cmmentioning
confidence: 99%
“…[22][23][24][25] Concomitant ATTR amyloidosis and severe aortic stenosis has been reported to be a relatively common finding in the elderly Indian population. 26 For hereditary ATTR in the Asian population, Ala97Ser (p.A97S) appears to be the most commonly identified mutation 23,24 | 899 (p.His108Arg), and ATTR-A97S (p.Ala117Ser). 23 Of note, ATTR p.A97S has been described as cardiomyopathy as well as a polyneuropathic syndrome.…”
Section: Suspecting Attr-cmmentioning
confidence: 99%
See 1 more Smart Citation